Instagram Naming Phenomena among Adult and Children (European Journal of Behavioral Sciences, 2019)
Creating a username on Instagram is also a unique phenomenon among children and adults and analyzing how children and adult naming their Instagram will be the main focus of this research. Apparently children and adults have a different way of thinking and social interaction circle. Children could not use variation in creating an Instagram username yet caused by limited social interaction they have in society however they use a combination of punctuation or numbers as a form of their creativity. Unlike the adult who has many different social circles, their Instagram naming pattern also varies.